A naphthol‐based fluorescence turn‐on sensor for detecting Ga(III) and its application to test strips. (10th January 2022) - Jung, Sumin; Lee, Jae Jun; Kim, Cheal
Abstract: A new naphthol‐based chemosensor NPN ((E)‐2‐(((2‐hydroxynaphthalen‐1‐ylmethylene)amino)isoindoline‐1, 3‐dione) was synthesized. NPN could sense Ga 3+ by a fluorescence "turn‐on" method from colorless to blue. Detection limit for Ga 3+ by NPN was determined to be 0.26 μM. The sensing mode of NPN and Ga 3+ turned out to be a 1:1. NPN could also be successfully applied to visible fluorescent test strips. The sensing process of Ga 3+ by NPN was illustrated through 1 H NMR titration, Job plot, ESI‐MS, and DFT calculations. Abstract :